PENGEMBANGAN MODEL PERMAINAN TEORI GROOS DALAM MENGEMBANGKAN ASPEK BAHASA ANAK USIA DINI - Kholila, Azmatul; Khadijah, Khadijah (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
Play cannot be separated from the world of early childhood. Early childhood is synonymous with playing and exploring the world around them. It doesn't matter whether it's hot or rainy, clean or dirty, anything that looks interesting can be used as material for experimentation. Play activities for young children are not only for training muscle strength, but more than that, playing will help children develop optimally. Because in this age range all aspects of children's development play an important role in stimulating their development, one aspect of early childhood development that needs to be developed is the language aspect. Language is the only means of communication for children to convey what they feel. The stimulation carried out can be in the form of providing games that can develop language aspects of early childhood. There are lots of games that can be played to support early childhood language development, such as role playing, guessing pictures, guessing faces, telling stories and so on. This research aims to determine the game model in developing aspects of children's language using Gross's theory. The research method used is a literature review taken from several articles about language development and children's language play practices